EVALUASI PENYELENGGARAAN PENDIDIKAN AGAMA ISLAM (PAI) DI UNIVERSITAS HASANUDDIN MAKASSAR, SULAWESI SELATAN: EVALUATION OF THE ISLAMIC RELIGIOUS EDUCATION (PAI) AT THE HASANUDDIN UNIVERSITY, MAKASSAR, SOUTH SULAWESI - Farida Hanun (Balai Penelitian dan Pengembangan Agama Jakarta, 2016)
This study aims to evaluating the implementation of Islamic religious education (PAI) in Public Higher Education. This research conducted at the Hasanuddin University, Makassar, South Sulawesi, by employing qualitative method. Data was collected by interviews and document analysis. The results of this study show that: (a) Universities need to develop a curriculum of Islamic Religious Education (PAI) that are tailored to local needs and conditions of the society, (b) PAI lecturer competence require for improvement through workshop and training programs, (c) the students continue to consider that PAI subject is unattractive, (d) mentoring activities which related to Islamic studies have shown a positive impact in ‘enriching and coloring’ Islamic life on campus, and (e) there is a significant needs for upgrading the multimedia devices for PAI teaching and learning process. Keywords: Evaluation of education, Islamic religious education, religious education at university level, Makassar. >Penelitian ini bertujuan untuk untuk mengevaluasi penyelenggaraan pendidikan Agama di Perguruan Tinggi Umum. Penelitian dilakukan di Universitas Hasanuddin Makassar dengan metode kualitatif. Pengumpulan data dilakukan dengan wawancara dan studi dokumen. Hasil penelitian menunjukkan: (a) Perguruan Tinggi perlu mengembangkan kurikulum Pendidikan Agama Islam (PAI) yang disesuaikan dengan kebutuhan dan kondisi lokal masyarakat, (b) kompetensi dosen PAI belum maksimal, perlu peningkatan kualitas melalui penyelenggraan Diklat Dosen PAI, (c) mahasiswa masih menganggap perkulihan PAI tidak menarik, (d) kegiatan mentoring memiliki dampak positif dalam mewarnai kehidupan keislaman di kampus, dan (e) sarana multimedia untuk pembelaajran PAI perlu ditingkatkan. Kata Kunci: Evaluasi pendidikan, Pendidikan Agama Islam, pendidikan agama di Perguruan Tinggi, Makassar.